Using the Doubly Charged Selected Ion Coupled with MS/MS Fragments Monitoring (DCSI-MS/MS) Mode for the Identification of Gelatin Species. (13th March 2014) - Cheng, Xian-Long; Wei, Feng; Chen, Jia; Li, Ming-hua; Zhang, Lei; Zhao, Ying-Yong; Xiao, Xin-Yue; Ma, Shuang-cheng; Lin, Rui-Chao
Abstract : In electrospray ionization (ESI) mode, peptides and proteins can be multiply charged ions; in this situation a doubly charged selected ion (DCSI) coupled with mass spectrometry (MS/MS) fragments monitoring (DCSI-MS/MS) method is the most suitable scanning mode to detect known peptides in complex samples when an ion-trap mass spectrometer is the instrument used for the analysis. In this mode, the MS detector is programmed to only select a doubly charged ion as a precursor and to perform continuous MS/MS on one or more of the selected precursors, either during a specific time interval or along the whole chromatographic run. Gelatin is a mixture of high molecular weight polypeptides from the hydrolysis of collagen. In this study, the DCSI-MS/MS monitoring mode was applied to the detection of previously characterized species-specific peptides from different gelatins. The proposed methodology makes use of tryptic digestion for sample preparation and peptide separation and identification by rapid resolution liquid chromatography coupled to an ion trap working in the DCSI-MS/MS mode for the analysis. This methodology was applied to the differential classification of five commercial, homological species of gelatins and proved to be an excellent tool for gelatin product authentication.